K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 1 2017

-2x=2
x=-1

3 tháng 1 2017

7-3x=9-x

<=>7-9=-x+3x

<=>-2=2x

=>x=-2:2

=>x= -1

6 tháng 2 2019

dễ mà ko biết làm

21 tháng 4 2020

Ta có: (3x - 9)(2x - 7) = (3x - 9)(4x + 3)

<=> 6x2 - 39x + 63 =  12x2 - 27x - 27

<=> 6x2 - 39x + 63 - 12x2 + 27x + 27 = 0

<=> -6x2 - 12x + 90 = 0

<=> -6(x2 + 2x - 15) = 0

<=> x2 + 5x  - 3x - 15 = 0

<=> x(x + 5) - 3(x + 5) = 0

<=> (x - 3)(x + 5) = 0

<=> \(\orbr{\begin{cases}x-3=0\\x+5=0\end{cases}}\)

<=> \(\orbr{\begin{cases}x=3\\x=-5\end{cases}}\)

Vậy pt có tập nghiệm là {3; -5}

21 tháng 4 2020

(3x - 9)(2x -7) = (3x-9)(4x-3)

(3x-9)(2x-7) - (3x-9)(4x-3)=0

(3x-9)(2x-7 - 4x +3)=0

(3x-9)(-2x - 4)=0

3(x-3)(-2)(x+2)=0

(x-3)(x+2)=0

=> x-3=0 hoặc x+2=0

=> x=3 hoặc x=-2

25 tháng 8 2020

a) ( 3x + 2 )( x - 1 ) - ( x + 2 )( 3x + 1 ) = 7

<=> 3x2 - x - 2 - ( 3x2 + 7x + 2 ) = 7

<=> 3x2 - x - 2 - 3x2 - 7x - 2 = 7

<=> -8x - 4 = 7

<=> -8x = 11

<=> x = -11/8

b) ( 6x + 5 )( 2x + 3 ) - ( 4x + 3 )( 3x - 2 ) = 8

<=> 12x2 + 28x + 15 - ( 12x2 + x - 6 ) = 8

<=> 12x2 + 28x + 15 - 12x2 - x + 6 = 8

<=> 27x + 21 = 8

<=> 27x = -13

<=> x = -13/27 

c) 2x( x + 3 ) - ( x + 1 )( 2x + 1 ) - 5 = 9

<=> 2x2 + 6x - ( 2x2 + 3x + 1 ) - 5 = 9

<=> 2x2 + 6x - 2x2 - 3x - 1 - 5 = 9

<=> 3x - 6 = 9

<=> 3x = 15

<=> x = 5

d) ( 5x + 3 )( 4x - 7 ) - ( 10x + 9 )( 2x - 3 ) = 10

<=> 20x2 - 23x - 21 - ( 20x2 - 12x - 27 ) = 10

<=> 20x2 - 23x - 21 - 20x2 + 12x + 27 = 10

<=> -11x + 6 = 10

<=> -11x = 4

<=> x = -4/11

25 tháng 8 2020

a, \(\left(3x+2\right)\left(x-1\right)-\left(x+2\right)\left(3x+1\right)=7\Leftrightarrow-8x-4=7\Leftrightarrow x=-\frac{11}{8}\)

b, \(\left(6x+5\right)\left(2x+3\right)-\left(4x+3\right)\left(3x-2\right)=8\Leftrightarrow27x+21=8\Leftrightarrow x=-\frac{13}{27}\)

c, \(2x\left(x+3\right)-\left(x+1\right)\left(2x+1\right)-5=9\Leftrightarrow3x-6=9\Leftrightarrow x=5\)

d, \(\left(5x+3\right)\left(4x-7\right)-\left(10x+9\right)\left(2x-3\right)=10\Leftrightarrow-11x+6=10\Leftrightarrow x=-\frac{4}{11}\)

b, \(\left(x-5\right)\left(x-4\right)-\left(x+1\right)\left(x-2\right)=7\)

\(\Rightarrow x^2-9x+20-x^2+x+2=7\)

\(\Rightarrow-8x+22=7\)

\(\Rightarrow-8x=-15\)

\(\Rightarrow x=\frac{15}{8}\)

c, \(\left(3x-4\right)\left(x-2\right)=3x\left(x-9\right)-3\)

\(\Rightarrow3x^2-10x+8=3x^2-27x-3\)

\(\Rightarrow3x^2-10x-3x^2+27x=\left(-3\right)+\left(-8\right)\)

\(\Rightarrow17x=-11\)

\(\Rightarrow x=-\frac{11}{17}\)

d, \(\left(x-3\right)\left(x^2+3x+9\right)+x\left(5-x^2\right)=6x\)

\(\Rightarrow x^3+3x^2+9x-3x^2-9x-27+5x-x^3=6x\)

\(\Rightarrow6x=-27\)

\(\Rightarrow x=-\frac{27}{6}\)

\(\Rightarrow x=-\frac{9}{2}\)

e, \(\left(3x-5\right)\left(x+1\right)-\left(3x-1\right)\left(x+1\right)=x-4\)

\(\Rightarrow3x^2-2x-5-3x^2-2x+1=x-4\)

\(\Rightarrow-4=x-4\)

\(\Rightarrow x=0\)

9 tháng 7 2019

b)    (x - 5)(x - 4) - (x + 1)(x - 2) = 7
<=> x2 - 9x + 20 - x2 + x + 2 - 7 = 0
<=> 8x - 15 = 0 <=> x = 15/8

c)    (3x - 4)(x - 2) = 3x(x - 9) - 3
<=> 3x2 - 10x + 8 = 3x2 - 27x - 3
<=> 17x = -11 <=> x = -11/17

d)    (x - 3)(x2 + 3x + 9) + x(5 - x2) = 6x
<=> x3 - 27 - x3 + 5x - 6x = 0
<=> x = -27

e)    (3x - 5)(x + 1) - (3x - 1)(x + 1) = x - 4
<=> (x + 1)(3x - 5 - 3x + 1) - x + 4 = 0
<=> -4x - 4 - x + 4 = 0 <=> x = 0

9 tháng 7 2019

b) \(\left(x-5\right)\left(x-4\right)-\left(x+1\right)\left(x-2\right)=7\)

\(\Leftrightarrow\) \(x^2-4x-5x+20-x^2+2x-x+2\)\(=7\)

\(\Leftrightarrow\) \(-8x+22=7\)

\(\Leftrightarrow\) x= \(\frac{-15}{8}\)

9 tháng 7 2019

c) \(\left(3x-4\right)\left(x-2\right)=3x\left(x-9\right)-3\)

\(\Leftrightarrow\)\(3x^2-6x-4x+8=3x^2-27x-3\)

\(\Leftrightarrow\) \(3x^2-3x^2-6x-4x+27x=-3-8\)

\(\Leftrightarrow\) \(17x=-11\)

\(\Leftrightarrow\) \(x=\frac{-11}{17}\)